The CNK1 scaffold binds cytohesins and promotes insulin pathway signaling - Lim, Junghwa (Cold Spring Harbor Laboratory Press, 2010)
Protein scaffolds play an important role in signal transduction, regulating the localization of signaling components and mediating key protein interactions. Here, we report that the major binding partners of the Connector Enhancer of KSR 1 (CNK1) scaffold are members of the cytohesin family of Arf guanine nucleotide exchange factors, and that the CNK1/cytohesin interaction is critical for activation of the PI3K/AKT cascade downstream from insulin and insulin-like growth factor 1 (IGF-1) receptors. We identified a domain located in the C-terminal region of CNK1 that interacts constitutively with the coiled-coil domain of the cytohesins, and found that CNK1 facilitates the membrane recruitment of cytohesin-2 following insulin stimulation. Moreover, through protein depletion and rescue experiments, we found that the CNK1/cytohesin interaction promotes signaling from plasma membrane-bound Arf GTPases to the phosphatidylinositol 4-phosphate 5-kinases (PIP5Ks) to generate a PIP(2)-rich microenvironment that is critical for the membrane recruitment of insulin receptor substrate 1 (IRS1) and signal transmission to the PI3K/AKT cascade. These findings identify CNK1 as a new positive regulator of insulin signaling.